Expanding the Differential Diagnosis of the Painful Nail: A Case of an Onychopapilloma with Neuroma - Jade Conway; Cynthia M. Magro; Shari R. Lipner (Case Reports in Dermatology, 2024)
Introduction: Onychopapilloma most commonly presents as longitudinal erythronychia, but diagnosis may be challenging in some cases due to varied clinical presentations. Most patients with onychopapillomas do not report associated pain but instead more commonly report functional interference. Case Report: We present a case of a 74-year-old female with a 5-year history of splitting and lifting of the right thumbnail, accompanied by nail sensitivity and intermittent painful throbbing. Clinical examination was significant for a less than 1 mm red line with distal onycholysis. Love’s test and a cold test performed with ice pack were negative. X-ray of the right thumb was negative for erosion or exostosis. Nail biopsy was performed, and dermatopathology was consistent with onychopapilloma with a concomitant traumatic neuroma. Conclusion: We report a case of onychopapilloma with a concomitant traumatic neuroma. Subungual neuromas are extremely rare and have not previously been associated with onychopapilloma. Our case supports the expansion of the differential diagnosis for a painful nail and demonstrates the importance of diagnostic confirmation with biopsy and histopathology.